TAWZIF ALMASADIR ARRAQMIAT FI TA’LIM AL'ADAB AL’ARABII LINNAATIQIN BIGHAIRIL ARABIAH - Annu'aimy, Anas Hisam Saeed (El-Tsaqafah : Jurnal Jurusan PBA, 2024)
This study presents an attempt to employ digital resources in teaching Arabic literature to non-Arabic speakers, as it seeks to demonstrate the importance of these resources and their role in enhancing the learning of Arabic literature through the capabilities offered by them that were not available in paper sources and traditional methods in teaching Arabic literature, especially for non-Arab students. In addition to the enormous capabilities and various sources offered by these resources, these resources that are provided through modern technology increase students' motivation towards learning, make the lesson more interesting and interactive for learners due to the digital, written, audio and visual resources they provide, with the possibility of re-listening to selected texts and controlling the speed of diction to suit the level of the non-Arabic speaking student, as well as the availability of literary dictionaries, sources and references to the mothers of literary books that enable the student to understand and assimilate literary texts and help him in his research studies. In education, the second topic deals with the most important digital resources available on the Internet and how to employ and benefit from them in teaching Arabic literature to non-Arabic speakers